A New Basal Sauropodomorph (Dinosauria: Saurischia) from Quebrada del Barro Formation (Marayes-El Carrizal Basin), Northwestern Argentina - Apaldetti, Graciela Cecilia (2011)
Background: Argentinean basal sauropodomorphs are known by several specimens from different basins; Ischigualasto, El Tranquilo, and Mogna. The Argentinean record is diverse and includes some of the most primitive known sauropodomorphs such as Panphagia and Chromogisaurus, as well as more derived forms, including several massospondylids. Until now, the Massospondylidae were the group of basal sauropodomorphs most widely spread around Pangea with a record in almost all continents, mostly from the southern hemisphere, including the only record from Antarctica. Methodology/Principal Finding: We describe here a new basal sauropodomorph, Leyesaurus marayensis gen. et sp. nov., from the Quebrada del Barro Formation, an Upper Triassic-Lower Jurassic unit that crops out in northwestern Argentina. The new taxon is represented by a partial articulated skeleton that includes the skull, vertebral column, scapular and pelvic girdles, and hindlimb. Leyesaurus is diagnosed by a set of unique features, such as a sharply acute angle (50 degrees) formed by the ascending process of the maxilla and the alveolar margin, a straight ascending process of the maxilla with a longitudinal ridge on its lateral surface, noticeably bulging labial side of the maxillary teeth, greatly elongated cervical vertebrae, and proximal articular surface of metatarsal III that is shelf-like and medially deflected. Phylogenetic analysis recovers Leyesaurus as a basal sauropodomorph, sister taxon of Adeopapposaurus within the Massospondylidae. Moreover, the results suggest that massospondylids achieved a higher diversity than previously thought. Conclusions/Significance: Our phylogenetic results differ with respect to previous analyses by rejecting the massospondylid affinities of some taxa from the northern hemisphere (e.g., Seitaad, Sarahsaurus). As a result, the new taxon Leyesaurus, coupled with other recent discoveries, suggests that the diversity of massospondylids in the southern hemisphere was higher than in other regions of Pangea. Finally, the close affinities of Leyesaurus with the Lower Jurassic Massospondylus suggest a younger age for the Quebrada del Barro Formation than previously postulated.